-11f=7(1-2d)+5

Simple and best practice solution for -11f=7(1-2d)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11f=7(1-2d)+5 equation:


Simplifying
-11f = 7(1 + -2d) + 5
-11f = (1 * 7 + -2d * 7) + 5
-11f = (7 + -14d) + 5

Reorder the terms:
-11f = 7 + 5 + -14d

Combine like terms: 7 + 5 = 12
-11f = 12 + -14d

Solving
-11f = 12 + -14d

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by '-11'.
f = -1.090909091 + 1.272727273d

Simplifying
f = -1.090909091 + 1.272727273d

See similar equations:

| 7x+5=-2x-40 | | -27=-r-10 | | x+2.8y=847.70 | | 8x+20=2x+10 | | x^2-11x+24=6 | | y+2.8x=847.70 | | 92+1+13x=180 | | -3x-4=5y-8 | | 5+10(-10x-9)=-3 | | 2/5=4/5(c) | | 6cos(6x)sin(7y)=7 | | Cos(2x)-cos(4x)=o | | 44x+2+90=180 | | 48/(-8) | | 4(2y+4)=3(y-6) | | -28=4/5(d) | | 4+11x=-40 | | x+57+x+137=180 | | 6x+11y-10x-8y+9x-7y= | | 4+5(-3x+7)=-9 | | (.1-x)*(.2-x)= | | 48/(-18) | | 50-8x=-6 | | 26+(2y+1)= | | -2=8y+3(y+3) | | (7x-4)(3x+9)=0 | | (x+2)(5x+6)=0 | | -10x+10=-40 | | -5.2(4s+6)-1.7(2s-4)= | | 3(2x+15)=2x+20 | | -5-8x=5 | | 2.8x+1y=747.7 |

Equations solver categories